A retrospective cohort study on the efficacy and safety of percutaneous vertebroplasty combined with bone-filling mesh container in vertebral metastases with posterior wall defect - Zhan, Ke; Chen, Ke; Gao, Guoyong; Xiang, Yucheng (Frontiers in Oncology, 2024)
Background To evaluate the clinical safety and efficacy of percutaneous vertebroplasty (PVP) combined with bone filled mesh container (BFMCs) for vertebral metastases with posterior wall defect. Methods From January 2019 to December 2021, patients with vertebral metastases and posterior wall defect that received operation of BFMCs in combine with PVP were included. The visual analogue scale (VAS) scores and Oswestry disability index (ODI) scores were evaluated before and 72 hours after operation, respectively. Post operational X-ray and CT scan were conducted to observe bone cement leakage and complications were recorded. Follow-up CT and MRI were obtained to evaluate the condition of the operated vertebrae and recurrence or progression of other bone metastases. Results 43 patients with 44 operated vertebrae were included. All patients successfully completed the surgery. The average VAS score decreased from 7.35±0.78 to 1.63±0.93 (p<0.05), and the ODI score decreased from 80.06±8.91 to 32.5±4.87 (p<0.05). Bone cement leakage were observed in 18 operated vertebrae, which were all asymptomatic. No intraspinal leakage, postoperative spinal nerve compression, pulmonary embolism or other serious complications were recorded. 21 patients had a followed-up of more than 1 year, with no operated vertebrae progression, 13 target vertebrae showing obvious sclerosis and necrosis, and no adjacent pathological fracture occurred. 16 of these patients had different degree of bone metastasis of other sites other than the operated vertebrae. Conclusion For spinal metastases with posterior wall defect, PVP combined with BFMCs was highly safe, and can effectively relieve pain for patients. 1 year follow-up showed local antitumor effect.